Clinical characteristics of patients with essential tremor or essential tremor plus. (6th January 2020) - Huang, Hongyan; Yang, Xinglong; Zhao, Quanzhen; Ning, Pingping; Shen, Qiuyan; Wang, Hui; Xie, Dan; Lu, Haitao; Xu, Yanming
Abstract : Background: The International Parkinson and Movement Disorder Society introduced the category of essential tremor (ET)‐plus in its new ET classification scheme, but how the clinical correlates of ET‐plus differ from those of "pure" ET is unclear. By comparing the clinical characteristics of ET and ET‐plus patients, we expect to better understand the impact and invoked questions of the new classification on clinical practice. Methods: We reviewed the medical records of 280 ET syndrome patients in an ongoing cross‐sectional study in a Chinese population and reclassified them according to the new criteria. Clinico‐demographic characteristics were compared between ET and ET‐plus patients. Risk factors of diagnosis of ET‐plus were explored using logistic regression. Results: A total of 121 patients (50.8%) were reclassified as having ET and 117 as having ET‐plus. ET‐plus group was significantly older at tremor onset, less educated, and more likely to have cranial tremor, depression symptom, anxiety symptom, and probable REM sleep behavior disorder. ET‐plus group also showed more severe upper limb tremor and cognition impairment. Regression analysis identified four independent risk factors associated with ET‐plus: late tremor onset (OR 3.04, 95%CI 1.60‐5.79), less educated (OR 0.91, 95%CI 0.85‐0.97), severe upper limb tremor (OR 2.46, 95%CI 1.30‐4.62), and presence of cranial tremor (OR 2.30, 95%CI 1.20‐4.41). Conclusions: The new classification scheme emphasized that ET syndrome is heterogeneous. ET‐plus cannot be seen as a subtype or a diagnosis of ET syndrome, but rather as a placeholder, representing an area of current scientific uncertainty.